CENTRAL VENOUS ACCESS: A COMPREHENSIVE REVIEW - Silva, Pedro Pinheiro Cardoso da (2024)
Central venous access is a medical procedure used to insert a catheter into a larger-caliber vein, usually located near the heart. This provides a direct route for the administration of fluids, medications, and parenteral nutrition. There are several techniques for performing central venous access, including percutaneous puncture, the Seldinger technique, and cut-down technique. Each technique has its specific indications and contraindications. Although it is a common intervention, central venous access is not without risks and complications, such as vascular injuries, infections, and thrombosis. Therefore, a multidisciplinary approach involving physicians, nurses, and other healthcare professionals is essential to ensure the safety and effectiveness of this procedure.